2019
DOI: 10.1136/bmjopen-2018-026077
|View full text |Cite
|
Sign up to set email alerts
|

Patient acceptability of three different central venous access devices for the delivery of systemic anticancer therapy: a qualitative study

Abstract: Objective Three types of central venous access devices (CVADs) are routinely used in the delivery of intravenous systemic anticancer therapy (SACT): peripherally inserted central catheters (PICCs), subcutaneously tunnelled central catheters (Hickman-type devices) and totally implantable chest wall ports (Ports). This qualitative study, nested within a multicentre, randomised controlled trial, sought to explore patient acceptability and experiences of the three devices. Design Eight focus groups were audio-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 22 publications
3
3
0
1
Order By: Relevance
“…In the present study, skin tunnelled catheters were reported by parents and adolescents to require more self-management than totally implanted ports because of the need for regular dressing changes, cleaning and flushing of the lines, and maintaining the cleanliness of the access port and clamps to avoid infection. These findings reflect those found amongst an adult population with central venous access devices ( Ryan et al., 2019 ). Participants in the present study tended to accept the care requirements of a skin tunnelled catheter without much complaint, and none was in a position to compare this with managing a totally implanted port which, because of its embedded position under the skin, required considerably less management.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the present study, skin tunnelled catheters were reported by parents and adolescents to require more self-management than totally implanted ports because of the need for regular dressing changes, cleaning and flushing of the lines, and maintaining the cleanliness of the access port and clamps to avoid infection. These findings reflect those found amongst an adult population with central venous access devices ( Ryan et al., 2019 ). Participants in the present study tended to accept the care requirements of a skin tunnelled catheter without much complaint, and none was in a position to compare this with managing a totally implanted port which, because of its embedded position under the skin, required considerably less management.…”
Section: Discussionsupporting
confidence: 87%
“…The adolescents with totally implanted ports and their parents were very positive about the freedom to engage fully in everyday life that an implanted port offered. This freedom has been previously documented in literature on central venous access devices amongst child ( Mangum et al., 2013 ) and adult populations ( Ryan et al., 2019 ; Ivziku et al., 2022 ).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Most participants faced practical challenges, especially adapting showering to keep the PICC dressing dry in the shower. Many of the practical challenges and supports required to adapt daily life support previous research that has documented the experience of people with a PICC [ 9 , 10 , 12 , 13 , 15 , 19 ]. Participants also raised other practical challenges they faced, such as modifying exercise, parenting, and sexual relationships which have not been identified previously.…”
Section: Discussionmentioning
confidence: 99%
“…Both cohorts have reported that adapting usual tasks, such as showering, to prevent complications [ 9 – 14 ]. Similarly, individuals receiving treatment for cancer and infection with a PICC have indicated that they felt underprepared for life with the device and described challenges understanding PICC information [ 11 , 12 , 15 ]. Research in both cohorts has found that some people face psychological challenges with accepting the PICC, as well as perceived stigma from the device, resulting in a need to conceal the PICC from view [ 10 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%